9 - The Case for a Modest Assessment of the International Criminal Justice Processes in Rwanda, Sierra Leone, and Some Lessons for Liberia - Jalloh, Charles Chernor; Morgan, Andrew (Africa Development, 2021)
This article seeks to evaluate the role and contributions of the UN International Criminal Tribunal for Rwanda (ICTR) and the Special Court for Sierra Leone (SCSL) to the task of dispensing justice to those most responsible for the commission of international crimes during the Rwandan and Sierra Leonean conflicts. The authors contrast those two situations to that of Liberia, where a Truth and Reconciliation Commission was set up in lieu of criminal accountability. The article argues that part of the unfair criticism of international criminal law is driven by the unrealistic expectation that ad hoc criminal courts such as the ICTR and the SCSL should not only dispense credible justice, but also help to restore peace and promote national reconciliation in deeply divided post-conflict societies. The article posits that even in best case scenarios, such courts can only mete out justice to individual perpetrators of horrific crimes in fair trials that comply with their statutes and international human rights law. An argument is therefore made for a return of these courts to their primary intended roles as criminal courts. Towards that end, the work of the ICTR and the SCSL are tested against eight factors relevant to assessing their achievements and limitations as criminal courts. The article shows that those special tribunals made important contributions to the process of justice for victims of atrocity crimes in Rwanda and Sierra Leone.